A Framework of National Pharmacovigilance System for Developing Countries - Nikookalam, Maryam; Hosseini, Azamossadat; Moghaddasi, Hamid; Asadi, Farkhondeh; Zarghi, Afshin (Iranian Journal of Pharmaceutical Sciences, 2024)
Pharmacovigilance is defined as “the science and activities related to the detection, assessment, understanding, and prevention of adverse drug reactions or any other drug-related problems”. The framework of the national pharmacovigilance system illustrates the general pattern of how the health system approaches the care of health products, defines the philosophy of supervision and policy orientation, and outlines the structure and development priorities of pharmacovigilance. The present study was conducted with the aim of presenting a framework of the national pharmacovigilance system framework for developing countries. The present study is of an applied study that was conducted descriptively in 2023. To present a framework of the national pharmacovigilance system framework, the main components of the national pharmacovigilance system framework were first identified and determined through a review of valid scientific sources and texts and national pharmacovigilance systems of the countries under study, considering the conditions and requirements of these countries. Then, the proposed model was put to the opinion of 65 experts for validation, and the Delphi method was implemented with a three-point scale in two rounds. Based on the results of the present study, the main components of the national pharmacovigilance system framework include: functions, infrastructure, and network. Each component includes sub-components and related operations and was agreed upon by experts with an average agreement rate of 95%. The framework of the national pharmacovigilance system is essential as a guide for the implementation of the national pharmacovigilance system. This framework enables a comprehensive evaluation of the structures and national and regional institutions affecting pharmacovigilance and can lead to the optimal implementation of the national pharmacovigilance system in developing countries. The national pharmacovigilance system can reduce drug-related problems, and its ultimate result can be a reduction in mortality and morbidity rates.